Integrating Agronomic and Molecular Advancements to Enhance Nitrogen Use Efficiency (NUE) and Promote Sustainable Rice Production - Uttam Bahadur Kunwar; Nazer Manzoor; Jiancheng Wen; Naba Raj Pandit (Nitrogen)
Rice is a major crop for half of the world’s population, and nitrogen (N) fertilizers play a crucial role in its production. However, imbalanced N fertilizer uses and traditional fertilization practices have led to low nitrogen use efficiency (NUE), increased N footprints, and reduced rice yields and farmers’ income. There are limited studies where the integration of both agronomic and molecular advancements to enhance NUE is discussed, particularly in developing countries. This review highlights novel agronomic and molecular strategies to enhance NUE, rice yields, and profitability, while minimizing environmental impact. The agronomic strategies include the 4R Nutrient Stewardship framework, enhanced efficiency nitrogen fertilizers (EENFs), nano-fertilizers, biochar-based fertilizers, biological N fixation, and sensor-based fertilizer management in major rice-growing countries. The molecular mechanisms focus on N uptake, assimilation, and utilization, highlighting the role of hormones, key genes, transcription factors (TFs), and regulatory pathways. Moreover, we examine promising rice genotypes and cultivars with improved NUE and grain yield. Additionally, this paper offers deep insights into recent advancements in molecular genetics, such as multi-omics approaches (transcriptomics, metabolomics, and metagenomics), the Genome-Wide Association Study (GWAS), Quantitative Traits Loci mapping (QTLs), Single Nucleotide Polymorphisms (SNPs) analysis, and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR-Cas9)-mediated genome editing, which serve as valuable tools for developing rice cultivars with enhanced NUE and grain yield.